Recommendations regarding the selection and justification of ways to increase the level of military and economic security of Ukraine during martial law in the conditions of the Russian-Ukrainian war (24.02.22-30.09.22) - Semenenko, Oleh; Abramova, Maryna; Voronchenko, Ihor; Dobrovolskyi, Yuzef; Korotya, Volodymyr; Sovhiria, Tetiana (Social Development and Security, 2022)
Purpose: is the formation of effective recommendations for increasing the level of military and economic security (MES) of Ukraine in the conditions of martial law during the Russian-Ukrainian war. Method: the main methods of research are the grapho-analytical method, the method of expert evaluations, methods of statistical analysis and mathematical statistics, forecasting methods. Findings: methodical approach and recommendations for assessing the state of the MES, as well as developing recommendations for increasing the level of the MES of Ukraine in the conditions of martial law during the Russian-Ukrainian war. Theoretical implications: the main results of the research on the subject of the article are: a defined list of problems of increasing the level of the MES in the conditions of martial law; a methodical approach to assessing the imbalance between indicators of the internal and external MES, as well as recommendations for increasing the MES of Ukraine in war conditions.